Excess costs of alcohol-dependent patients in German psychiatric care compared with matched non-alcohol-dependent individuals from the general population: a secondary analysis of two datasets. Issue 8 (29th August 2018) - Dams, Judith; Buchholz, Angela; Kraus, Ludwig; Reimer, Jens; Scherbaum, Norbert; Konnopka, Alexander; König, Hans-Helmut
Abstract : Objectives: Heavy alcohol use can cause somatic and mental diseases, affects patients' social life and is associated with social isolation, unemployment and reduced quality of life. Therefore, societal costs of alcohol dependence are expected to be high. The aim of this study was to estimate excess costs of patients with alcohol dependence diagnosed using the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition criteria compared with individuals without alcohol dependence in Germany. Design: In a secondary analysis, baseline data of patients with alcohol dependence enrolled in a randomised controlled trial (German Clinical Trials Register DRS00005035) were compared with data collected via a telephone survey from individuals without alcohol dependence and that had been matched by entropy balancing. Health service use was evaluated retrospectively for a 6-month period. Settings: Four German psychiatric university clinics (patients with alcohol dependence) and the German general adult population (individuals without alcohol dependence). Participants: n=236 adult patients with alcohol dependence and n=4687 adult individuals without alcohol dependence. Primary and secondary outcome measures: The excess costs of health service use, absenteeism and unemployment of patients with alcohol dependence were calculated and compared with individuals without alcohol dependence. In subgroup analyses, the associations between excess cost and gender, comorbidities and the duration of disease were investigated. Results: Total 6-month excess costs of €11 839 (95% CI €11 529 to €12 147) were caused by direct excess costs of €4349 (95% CI €4129 to €4566) and indirect costs of €7490 (95% CI €5124 to €9856). In particular, costs of inpatient treatment, formal long-term care, absenteeism and unemployment were high. Conclusions: Alcohol dependence causes substantial direct and indirect excess costs. Cost-effective interventions to prevent and treat alcohol dependence are urgently needed. Trial registration number: DRKS00005035.